Natural killer cell development - Colucci, Francesco (Henry Stewart Talks, 2009)
Natural killer cells are versatile lymphocytes, NK cells functions are important in health and disease: reproduction, cancer, transplantation, infection and autoimmunity, Cell subsets, location and gene expression define functional heterogeneity, Development influenced by MHC, stroma, transcription factors and cytokines, Comparisons and contrasts between human and mouse NK cell development, Uterine NK cells as ultimate example of specialized lineages of NK cells